Efektifitas Enpowerment Education terhadap pengetahuan Melakukan Vaksinasi HPV pada Remaja Putri - Imelda, Fatwa; Karota, Evi; Tarigan, Mula (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Cervical cancer is one of the leading causes of death in developing countries such as Indonesia. One of the government prevention programs is HPV vaccination. HPV vaccination in adolescents has not been widely practiced by adolescents in Indonesia. Many factors influence the acceptance of HPV vaccination in adolescents. Efforts to increase HPV vaccination behavior in schools through Empowerment Education, can be an alternative intervention that can be done. Objective of the study: To analyze the effectiveness of Enpowerment Education on knowledge of HPV vaccination among adolescent girls. Research method: The research design was Quasi Experimental Design using Pre Post Design With A Comparison Group conducted from December 2023 to June 2024. Quantitative instruments using the knowledge questionnaire to do HPV vaccination have gone through validity and reliability tests with an Alpha Cronbach value> 0.6 Quantitative data analysis with the Wilcoxon Signed Test (paired) and the Mann Whitney Test (unpaired). Results: There is a difference in knowledge (P=0.000) to vaccinate Pre test and Post test in the Intervention group. There is a difference in knowledge (p=0.000) to do HPV vaccination (p=0.675) in the Post Test Group of Control and Intervention Groups Conclusion: Enpowerment Education has an effect on increasing knowledge of HPV vaccination. Enpowerment education can be used to improve the knowledge female students that can be used in schools. Keywords: Enpowerment Education, Knowledge, HPV  ABSTRAK Latar belakang: Kanker serviks menjadi salah satu penyebab kematian terbanyak di negara berkembang seperti Indonesia. Salah satu pencegahan program pemerintah adalah vaksinasi HPV. Vaksinasi HPV pada remaja belum banyak dilakukan oleh remaja di Indonesia. Banyak faktor yang mempengaruhi penerimaan untuk vaksinasi HPV pada remaja. Upaya peningkatan perilaku vaksinasi HPV di Sekolah melalui Empowerment Education, dapat menjadi suatu alternatif intervensi yang dapat dilakukan. Tujuan penelitian: Menganalisis Efektifitas Enpowerment Education terhadap pengetahuan melakukan vaksinasi HPV pada remaja putri. Metode penelitian: Desain penelitian adalah Quasi Experimental Design menggunakan Pre Post Design With A Comparison Group yang dilakukan dari Desember 2023 hingga Juni 2024 Instrumen kuantitatif menggunakan kuesioner pengetahuan melakukan vaksinasi HPV telah melalui uji validitas dan reliabilitas dengan nilai Alpha Cronbach >0.6 Analisis data dengan kuantitatif dengan uji Wilcoxon Signed Test  (berpasangan) dan uji Mann Whitney Test (tidak berpasangan). Hasil : Terdapat perbedaan pengetahuan ( P=0.000) melakukan vaksinasi  Pre test dan Post test pada kelompok Intervensi. Terdapat perbedaan pengetahuan (p=0.000 melakukan vaksinasi HPV pada kelompok Post Test Kelompok Kontrol dan Intervensi Kesimpulan : Enpowerment Education berpengaruh terhadap  pengetahuan melakukan vaksinasi HPV. Enpowerment education dapat digunakan untuk meningkatkan pengetahuan remaja putri di lingkungan sekolah. Kata Kunci: Enpowerment, Education, Pengetahuan, Vaksinasi, HPV